Pure laparoscopic donor right hepatectomy: brightening the dark side of the moon in the era of space travel - Hong, Suk Kyun; Lee, Kwang-Woong; Yi, Nam-Joon; Suh, Kyung-Suk (Laparoscopic Surgery, 2018)
We thank Pravisani et al. for their valuable comments on our recent article and for reviewing current perspectives in pure laparoscopic donor right hepatectomy (PLDRH) (1). Our responses to the issues raised are outlined below.